Sand fly fauna (Diptera: Psychodidae) from Serra da Mocidade Nacional Park: report of vectors and putative vectors of American cutaneous leishmaniasis and new records for the state of Roraima, Brazil - Ramos, Walkyria Rodrigues; de Oliveira, Arley Faria José; de Freitas, Rui Alves; Alves, Veracilda Ribeiro; Cordeiro, Danilo Pacheco (Zootaxa, 2018)
Phlebotomine sand flies are insects of medical importance, as they are vectors of viruses, bacteria and trypanosomatids of the genus Leishmania Ross, the causative agent of leishmaniasis (Forattini 1973). During the past 20 years approximately 500,000 cases of leishmaniasis have been reported in Brazil. Most of these cases were reported in the North and Northeast regions. In the State of Roraima, almost 2,000 cases, including both cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL), have been reported during the past three years (SINAN 2017). Usually the transmission by infected female sand flies occurs in wild or rural areas, but there have also been recorded cases and vector captures in urban environments. Some sand fly species are known to enter houses in search of resting places and blood meal sources; as a result of this behavior, they are remarkably adaptable to new environments (Carvalhoet al. 2010).